2020
DOI: 10.3390/polym12081765
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Polymers for Organ 3D Printing

Abstract: Three-dimensional (3D) printing, known as the most promising approach for bioartificial organ manufacturing, has provided unprecedented versatility in delivering multi-functional cells along with other biomaterials with precise control of their locations in space. The constantly emerging 3D printing technologies are the integration results of biomaterials with other related techniques in biology, chemistry, physics, mechanics and medicine. Synthetic polymers have played a key role in supporting cellular and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 170 publications
(282 reference statements)
0
62
0
2
Order By: Relevance
“…The non-ionic surfactant gelation temperature is dependent on its concentration and structure [ 114 ]. The main characteristics of this gel form are good biocompatibility, low cytotoxicity, weak mechanical properties, quick degradation rates, rapid dissolution in aqueous solutions, and poor cell viabilities [ 115 , 116 ]. In the area of tissue engineering, polaxamer hydrogels have been studied for diverse approaches in tissue regeneration [ 114 , 117 , 118 , 119 , 120 ].…”
Section: Printable Hydrogelsmentioning
confidence: 99%
“…The non-ionic surfactant gelation temperature is dependent on its concentration and structure [ 114 ]. The main characteristics of this gel form are good biocompatibility, low cytotoxicity, weak mechanical properties, quick degradation rates, rapid dissolution in aqueous solutions, and poor cell viabilities [ 115 , 116 ]. In the area of tissue engineering, polaxamer hydrogels have been studied for diverse approaches in tissue regeneration [ 114 , 117 , 118 , 119 , 120 ].…”
Section: Printable Hydrogelsmentioning
confidence: 99%
“…In the farther future, the innovation of 3D printing will constantly expand the potential of 3D bioprinting, and therefore the mutual enhancement of physical organ models and in vitro tissue models [ 212 , 213 ] will be more significant. 3D bioartificial organs [ 204 , 214 , 215 ] with complete organ functions will be the ultimate embodiment of the integration and development of these fields. Although there is still a long way to go, this is the inevitable pathway for organ models to go from “appearance resemblance” (having the same physical shape as real organs) to “spiritual resemblance” (having the same biological functions as real organs) that worth people making unremitting efforts.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For example, Gu et al [ 34 ] reported a reversible physical cross-linking strategy to accurately deposit gelatin methacrylic “bioinks” loaded with human chondrocytes at low concentrations without any sacrificial materials. Chen et al [ 35 ] introduced 1% aldehyde hyaluronic acid (AHA) and 0.375% N-carboxymethyl chitosan (CMC) to obtain a polysaccharide gelatin (GEL, 5%)-alginate (ALG, 1%) “bioink”. This GEL-ALG/CMC/AHA “bioink” has a weak temperature dependence when it was printed in vivo at about 37°C using traditional printing methods.…”
Section: Introductionmentioning
confidence: 99%